2022
DOI: 10.3389/fcell.2022.852135
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Omics Analysis of MCM2 as a Promising Biomarker in Pan-Cancer

Abstract: Minichromosome maintenance 2 (MCM2) is a member of the minichromosomal maintenance family of proteins that mainly regulates DNA replication and the cell cycle and is involved in regulating cancer cell proliferation in various cancers. Previous studies have reported that MCM2 plays a pivotal role in cell proliferation and cancer development. However, few articles have systematically reported the pathogenic roles of MCM2 across cancers. Therefore, the present pan-cancer study was conducted. Various computational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 61 publications
(62 reference statements)
0
7
0
Order By: Relevance
“…Recent studies have reported that abnormal expression of CAF-1 can promote tumorigenesis and drive tumor metastasis 12 14 . However, even though several genetic mutations in parental histone chaperones, such as MCM2 15 , 16 and POLA1 17 have been reported in a number of cancer patients, and POLE4 deficiency mice exhibit tumor predisposition 18 , whether parental histone inheritance plays a role in tumorigenesis or tumor evolution is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have reported that abnormal expression of CAF-1 can promote tumorigenesis and drive tumor metastasis 12 14 . However, even though several genetic mutations in parental histone chaperones, such as MCM2 15 , 16 and POLA1 17 have been reported in a number of cancer patients, and POLE4 deficiency mice exhibit tumor predisposition 18 , whether parental histone inheritance plays a role in tumorigenesis or tumor evolution is still unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have recently reported that MCM2 expression could affect the immune cell infiltration. For example, an analysis of The Cancer Genome Atlas data recently revealed that MCM2 is not only significantly upregulated as a component of the tumor mutation burden, which is commonly used as a biomarker for cancer immunotherapy, 21 in advanced stages of almost all cancers but also closely associated with the infiltration of various immune cells in melanoma 22 and hepatocellular carcinoma. 23 Overall, it was expected that the interplay of MCM2 expression and tumor microenvironment critically affects tumor evolution, which subsequently impacts patient survival and immunotherapy response.…”
Section: Discussionmentioning
confidence: 99%
“…MCM2 encodes a 904 amino acid protein with a molecular weight of 101896Da. MCM2 is a member of microchromosome maintenance protein family, regulates DNA replication and cell cycle by participating in formation of replication initiation complex [23][24][25]. Previous studies have shown that inhibition of MCM2 reduces cell viability and aggravates apoptosis in cellular models of Alzheimer's disease [26].…”
Section: Discussionmentioning
confidence: 99%